NEW TRENDS IN NUTRITIONAL SUPPORT IN PEDIATRICS - N.P. Shen’; D.V. Suchkov; Yu.Kh. Saifitdinov (Педиатрическая фармакология)
Adequate nutritional support of children in critical conditions is undoubtedly a recognised, efficient and evident method of preventing and correcting many complications at the intensive treatment stage. Unhealthy eating habits of patients in critical conditions facilitate the development of nutrition deficit, results in an increased risk of infectious complications and multiorgan failure, slows down the tissue repair processes and restoration of spontaneous breathing. The work describes the results of dietary studies in children in a critical situation. The authors demonstrate that age-adapted infant formulas for enteral feeding are highly efficient in correcting metabolic disorders related to wound processes and help improve the tolerance to a long-term chemotherapy. Key words: nutritional support, critical conditions, enteral nutrition, age-adapted formulas. (Pediatric Pharmacology. – 2010; 7(6):82-85)